Dua Sisi Proses Penyelesaian Sengketa: Upaya Mewujudkan Keadilan Pemilu (Studi Kasus di Bawaslu Kabupaten Purwakarta) - Ujang Abidin; Dulnasir Dulnasir (Muttaqien, 2022)
In accordance with the mandate of the regulation, the dispute resolution of the regional election and election processes is delegated by the supervisory and election justice enforcement agency, namely Bawaslu. The role of Bawaslu which is so central is the hope in maintaining the fairness of the regional and general elections. The writing of this article will focus on the comparison of the dispute resolution process in the 2018 Purwakarta Regional Elections and the 2019 Simultaneous Elections. The two dispute cases in different momentum make the process of seeking legal justice in political contestation worthy of attention. The type of research in this article is normative juridical law research with a case study conducted at Bawaslu, Purwakarta Regency, West Java Province. The results of the study can be concluded that the dispute resolution process in the regional elections and elections that occurred in the Bawaslu of Purwakarta Regency was guided by the regulations and legal facts in the trial. The pair of Rustandi and Dikdik as candidates for regent whose application was rejected by the KPU and Angga and Lukmanul Hakim as candidates for DPRD members who were removed from DCT by the KPU were also a legal process that was taken up by Bawaslu to make a decision that upholds a sense of justice. Keywords: Dispute Resolution, Bawaslu Purwakarta, DCT Strike